SNO+ Liquid Scintillator Characterization: Timing, Quenching, and Energy Scale - O'Sullivan, E; Wan Chan Tseung, H; Tolich, N; O'Keeffe, H; Chen, M (2012)
This contribution describes laboratory measurements designed to investigate the optical properties of linear alkybenzene (LAB). Presented here is the measurement of the scintillation light timing profiles due to alpha and beta-particle excitation, the calculation of alpha/beta discrimination capability based on these timing distributions, and the investigation of electron energy scale. © 2012 Elsevier B.V.